A game of dolly revival - Kuular, Viktor Sh. (The New Research of Tuva, 2013)
Abstract: An extract from the author’s book "Game of dolly revival. About the skill of making and playing dolly revival in indigenous culture of Russian Old Believers in Siberia” (M., 2011).
Keywords: game; dolls; folklore; children; the world of childhood